The human cystathionine beta-synthase (CBS) gene: complete sequence, alternative splicing, and polymorphisms - Kraus, Jan P; Oliveriusová, Jana; Sokolová, Jitka; Kraus, Eva; Vlček, Čestmír; de Franchis, Raffaella; Maclean, Kenneth N; Bao, Liming; Bukovská, Gabriela; Patterson, David; Pačes, Václav; Ansorge, Wilhelm; et al. (Genomics (San Diego, Calif.), 1998)
Cystathionine beta-synthase [CBS; l-serine hydro-lyase (adding homocysteine), EC 4.2.1.22] catalyzes the first committed step of transsulfuration and is the enzyme deficient in classical homocystinuria. In this report, we describe the molecular cloning and the complete nucleotide sequence of the human CBS gene. We report a total of 28,046 nucleotides of sequence, which, in addition to the CBS gene, contains approximately 5 kb of the 5' flanking region. The human CBS gene contains 23 exons ranging from 42 to 209 bp. The 5' UTR is formed by 1 of 5 alternatively used exons and 1 invariably present exon, while the 3' UTR is encoded by exons 16 and 17. We also describe the identification of two alternatively used promoter regions that are GC rich (approximately 80%) and contain numerous putative binding sites for Sp1, Ap1, Ap2, and c-myb, but lack the classical TATA box. The CBS locus contains an unusually high number of Alu repeats, which may predispose this gene to deleterious rearrangements. Additionally, we report on a number of DNA sequence repeats that are polymorphic in North American and European Caucasians. Copyright 1998 Academic Press.
Keywords: exony; Alu Elements; elementy Alu; sekvence nukleotidů; Sequence Homology, Nucleic Acid; cystathionin-beta-synthasa; Cystathionine beta-Synthase; vazebná místa; polymorfismus genetický; Cloning, Molecular; Exons; Sequence Analysis, DNA; klonování DNA; běloši; sekvenční analýza DNA; molekulární sekvence - údaje; sekvenční homologie nukleových kyselin; promotorové oblasti (genetika); Polymorphism, Genetic; White People; Binding Sites; lidé; Transcription Factors; alternativní sestřih; transkripční faktory; Humans; Promoter Regions, Genetic; Minisatellite Repeats; Molecular Sequence Data; Alternative Splicing; Base Sequence; minisatelitní repetice